2010
DOI: 10.1007/s12210-010-0100-6
|View full text |Cite
|
Sign up to set email alerts
|

The crystalline basement of the Adria microplate in the eastern Alps: a review of the palaeostructural evolution from the Neoproterozoic to the Cenozoic

Abstract: The frontal northern part of the continental Adriatic microplate is formed by a stack of Austroalpine nappes and by the Southalpine basement and cover units. Both basement portions are now side by side, separated by the Periadriatic (Insubric) fault system, but they became juxtaposed only during the Alpine orogeny. Permian HT-LP metamorphism is now recognised also within the Austroalpine basement of the eastern Alps, whilst it was known since long in the Southalpine basement. High thermal heat flow responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…Permo-Triassic continental gabbros are located in the Austroalpine and Southalpine domains of the whole Alpine realm ( Figure 2) and are associated with subcontinental peridotites emplaced at different structural levels ( Figure 4c and Table S2; Bonin et al, 1993;McCarthy & Muntener, 2015;Rottura et al, 1998;Spalla et al, 2014;Spiess, Cesare, Mazzoli, Sassi, & Sassi, 2010;Staehle et al, 2001). Although the gabbros are generally considered to be generated from variably contaminated mantle sources in an extensional tectonic regime under a high thermal state, associated with lithospheric thinning and rifting (Spalla et al, 2014, and references therein), from a geochemical point of view, most of the gabbros have a tholeiitic signature (Spalla et al, 2014, and references therein).…”
Section: Permo-triassic Continental Gabbrosmentioning
confidence: 99%
“…Permo-Triassic continental gabbros are located in the Austroalpine and Southalpine domains of the whole Alpine realm ( Figure 2) and are associated with subcontinental peridotites emplaced at different structural levels ( Figure 4c and Table S2; Bonin et al, 1993;McCarthy & Muntener, 2015;Rottura et al, 1998;Spalla et al, 2014;Spiess, Cesare, Mazzoli, Sassi, & Sassi, 2010;Staehle et al, 2001). Although the gabbros are generally considered to be generated from variably contaminated mantle sources in an extensional tectonic regime under a high thermal state, associated with lithospheric thinning and rifting (Spalla et al, 2014, and references therein), from a geochemical point of view, most of the gabbros have a tholeiitic signature (Spalla et al, 2014, and references therein).…”
Section: Permo-triassic Continental Gabbrosmentioning
confidence: 99%
“…Most of the pre-Alpine continental lithosphere recycled during the Alpine subduction shows a pre-Mesozoic metamorphic evolution compatible with the evolution of the European Variscan belt (von Raumer et al, 2003;Spalla and Marotta, 2007;Spiess et al, 2010;Spalla et al, 2014;Roda et al, 2018a). von Raumer et al (2003) suggested that the present day Alpine domains (Helvetic, Penninic, Austroalpine and Southalpine) were probably located along the northern margin of Gondwana.…”
Section: Variscan Tectono-metamorphic Evolution In the Alpsmentioning
confidence: 98%
“…The outcropping crystalline basement consists of metamorphic rocks (phyllades and mica-schists) and igneous granitic (s.l.) intrusions formed during the Variscan orogeny [9,10]. The basement is covered by Permian volcanics consisting of ignimbrites, mainly rhyolitic in composition, of the Athesian Volcanic Group [11,12], and by Triassic sedimentary rocks [13,14], sometimes crosscut by Early Triassic basic dykes [15].…”
Section: Geological Outlinesmentioning
confidence: 99%